Pre-lithiation method
By premature lithium carbon material using the lithium carbon material in the negative electrode of a lithium -ion battery, the problem of low efficiency of the lithium -ion battery Kuron is low in efficiency and achieve higher energy density and longer cycle life.
Patent Information
- Application Number
- CN202310892177.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-21
AI Technical Summary
During the first charging and discharging process of existing lithium-ion batteries, the generation of the negative electrode surface SEI consumes a lot of lithium, resulting in low efficiency for the first time, affecting the actual energy density of the battery, and limiting its large-scale commercial application.
The lithium carbon material with a cocoon structure is used as a pre -lithium -based material to pre -lithium -lithium the electrode to form a prefabricated electrode. The lithium carbon material of the cocoon structure includes a cocoon body formed by the structured carbon material and the lithium -containing particles contained in the cocoon body, which can improve the electrical and structural stability of the negative electrode.
By precisely controlling the amount of lithium supplement, the first Coulombic efficiency of lithium-ion batteries is improved, the cycle life is extended, the rate performance is enhanced, dendrite growth is suppressed, and the overall performance of the negative electrode is improved.
Smart Images

Figure CN119340511A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of energy storage technology, and in particular to a pre-lithiation method. Background Art
[0002] Lithium-ion batteries have the advantages of long cycle life, high energy density, and no memory effect. They are currently the most widely used secondary batteries. At present, the negative electrodes of lithium-ion batteries are commonly made of graphite, silicon-carbon materials, and silicon-oxygen materials. During the first charge and discharge process of lithium-ion batteries, SEI on the negative electrode surface consumes a large amount of lithium, resulting in a low first coulombic efficiency, causing a significant decrease in the actual specific energy of lithium-ion batteries, which seriously restricts the large-scale commercial application of lithium-ion batteries. Therefore, how to improve the first coulombic efficiency has become a research hotspot.
[0003] Some progress has been made in pre-lithiation using metallic lithium powder. Among them, Tesla's patent (CN108780887 B) discloses an electrode membrane comprising: carbon particles, elemental metal and fibrillated binder; wherein the electrode membrane is self-supporting and substantially free of solvent residue. The carbon particles include graphite particles, and the elemental metal includes elemental lithium metal particles. The preparation method comprises combining elemental lithium metal, a plurality of carbon particles and a fibrillated binder to form an electrode membrane mixture; and forming an electrode membrane from the electrode membrane mixture, i.e., pre-lithiation using metallic lithium powder mixed with graphite. Metallic lithium powder is too active and needs to be stabilized before use. A common method is to form a lithium carbonate layer or a lithium fluoride layer on its surface, such as the passivated lithium powder of FMC, but the lithium carbonate layer or the lithium fluoride layer has a low conductivity, and the metallic lithium powder forms voids in the negative electrode after taking effect, which not only reduces the conductivity of the negative electrode, but also may grow lithium dendrites in the thinner area of the negative electrode, which is not conducive to the improvement of the negative electrode performance.
[0004] How to develop a pre-lithiation method that can accurately control the amount of lithium replenishment, ensure stable structure after pre-lithiation, not significantly reduce conductivity, and inhibit dendrite growth has become an urgent problem to be solved at this stage. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a pre-lithiation method. The pre-lithiation method selects a lithium-carbon material with a cocoon structure as a lithium supplement, which significantly improves the first coulombic efficiency of a lithium-ion battery. The lithium-carbon material with a cocoon structure contains a structural carbon material with good conductivity and certain rigidity, which can improve the conductivity and structural stability of the pre-lithiation negative electrode.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] The present invention provides a pre-lithiation method, which includes pre-lithiation of an electrode using a lithium-carbon material with a cocoon structure as a pre-lithiation material (lithium supplement) to form a pre-lithiation electrode, wherein the lithium-carbon material with a cocoon structure includes a cocoon body formed by a structural carbon material and one or more lithium-containing particles contained in the cocoon body.
[0008] Optionally, the lithium-carbon material having a cocoon structure exists in the negative electrode active material layer and is distributed between the negative electrode active materials.
[0009] Optionally, the lithium-carbon material having a cocoon structure forms a pre-lithium layer, and the pre-lithium layer is located between the negative electrode active material layer and the current collector.
[0010] In the present invention, a lithium-carbon material with a cocoon structure is used as a pre-lithiation material for lithium supplementation, and lithium-containing particles are used as a lithium source to accurately supplement lithium to the negative electrode. The obtained pre-lithiation negative electrode has the advantages of high structural stability, long cycle life and good rate performance. Among them, the cocoon structure formed by the structural carbon material has certain rigidity and good conductivity, and can provide a stable electron path. When the lithium-carbon material is present in the negative electrode active material layer, it has good contact with the negative electrode active material, and can construct an electron path while playing a supporting role. Even after the lithium-containing particles are consumed, no obvious voids will be formed, and the internal resistance of the negative electrode will not be increased; the cocoon structure of the structural carbon material can also absorb and retain the electrolyte, so that the lithium-containing particles can fully exert their capacity, and overcome the defects of lithium supplementation by metal lithium powder. When the lithium-carbon material forms a pre-lithiation layer, the pre-lithiation layer formed by the lithium-carbon material with a cocoon structure has the characteristics of good viscosity, good ductility and high surface roughness, and is arranged between the current collector and the negative electrode active material layer, and is tightly combined with the current collector and the negative electrode active layer respectively, so as to improve the binding force between the current collector and the negative electrode active material layer.
[0011] Optionally, the negative electrode active material includes graphite, tin-based materials, hard carbon, soft carbon, activated carbon, mesophase carbon microspheres, silicon carbon (Si / C) materials or silicon oxygen (SiO x (0<x≤2)) Any one or a combination of at least two of the materials.
[0012] Optionally, the structural carbon material includes any one or a combination of at least two of granular, linear or flaky nanocarbon materials, preferably acetylene black, Ketjen black, Cabot BP2000, Super P, single-walled carbon nanotubes, few-walled carbon nanotubes, multi-walled carbon nanotubes, doped carbon nanotubes, graphene, doped graphene, carbon nanofibers or doped carbon nanofibers, preferably any one or a combination of at least two of single-walled carbon nanotubes, few-walled carbon nanotubes, multi-walled carbon nanotubes, doped carbon nanotubes, graphene or doped graphene.
[0013] Optionally, the doping elements in the doped carbon nanotubes, doped graphene or doped carbon nanofibers independently include any one of fluorine, nitrogen, oxygen, phosphorus, silver, silicon, tin or zinc, or a combination of at least two of them.
[0014] Optionally, the lithium-containing particles include metallic lithium particles and / or metallic lithium alloy particles, preferably metallic lithium alloy particles. A small amount of the metallic lithium alloy particles remain after lithium replenishment to form a skeleton, which cooperates with the structural carbon material and does not produce large voids in the negative electrode, thereby increasing the internal resistance of the negative electrode. At the same time, the deposition of metallic lithium can be regulated to improve the cycle performance of the negative electrode while achieving lithium replenishment.
[0015] Optionally, the mass content of metallic lithium in the metallic lithium alloy particles is not less than 70%, for example, it can be 70%, 72%, 75%, 80%, 83%, 85%, 88%, 90%, 93%, 95%, 97% or 99%, etc., including but not limited to the listed point values. If the mass content is too low, more inactive lithium substances will be introduced, affecting the energy density of the negative electrode, and preferably it is not less than 85%.
[0016] Optionally, the average particle size of the lithium-containing particles is 1-100 microns, for example, 1 micron, 3 microns, 5 microns, 10 microns, 15 microns, 20 microns, 25 microns, 30 microns, 40 microns, 50 microns, 60 microns, 70 microns, 80 microns, 90 microns or 100 microns, including but not limited to the listed point values, preferably 5-30 microns.
[0017] Optionally, the metallic lithium alloy particles include binary lithium alloys and / or ternary lithium alloys, the binary lithium alloy powder includes any one of lithium magnesium alloys, lithium boron alloys, lithium silver alloys, lithium indium alloys, lithium silicon alloys, lithium aluminum alloys or lithium tin alloys, or a combination of at least two of them; the ternary lithium alloy powder includes any one of lithium tin silver alloys, lithium silver silicon alloys or lithium boron zinc alloys, or a combination of at least two of them.
[0018] Optionally, the mass ratio of the structural carbon material to the lithium-containing particles is 1:(1-1000), for example, it can be 1:1, 1:5, 1:10, 1:20, 1:50, 1:55, 1:60, 1:80, 1:90, 1:100, 1:120, 1:150, 1:200, 1:300, 1:400, 1:450, 1:480, 1:500, 1:550, 1:600, 1:700, 1:800, 1:900, 1:950 or 1:1000, etc., including but not limited to the point values, preferably 1:(10-500).
[0019] Optionally, an organic conductive layer is provided between the lithium-containing particles and the structural carbon material, and the organic conductive layer includes an organic lithium ion conductive agent and a conductive agent. The organic conductive layer is conducive to the diffusion of lithium ions, and further improves the ionic conductivity of the pre-lithiation negative electrode.
[0020] The conductive agent includes at least one of carbon nanotubes, carbon black, graphene, and acetylene black. The organic lithium ion conductive agent includes polyethylene oxide, polyethylene glycol, polysiloxane, polytrimethylene carbonate, polycarbonate, polyethylene carbonate, polypropylene carbonate, polyvinylene carbonate, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, poly(vinylidene fluoride-hexafluoropropylene), polyphenylene sulfide, p-benzoquinone, and a copolymer or mixture of at least two of the above polymers.
[0021] The mass of the lithium-containing particles, the organic lithium ion transport agent and the conductive agent is (80-95): (1-
[0022] 10): (0.1-10), preferably (90-95): (5-10) (0.5-5).
[0023] Optionally, the mass ratio of the negative electrode active material to the lithium-carbon material with a cocoon structure includes but is not limited to 1g:(1-300)mg, for example, it can be 1g:1mg, 1g:3mg, 1g:5mg, 1g:10mg, 1g:15mg, 1g:20mg, 1g:30mg, 1g:50mg, 1g:100mg, 1g:120mg, 1g:150mg, 1g:180mg, 1g:200mg, 1g:240mg or 1g:300mg, etc., including but not limited to the point values. The mass ratio can be selected according to the type of negative electrode active material, the type of lithium-carbon material with a cocoon structure, the first coulomb efficiency and actual needs. Generally, the first coulomb efficiency of graphite negative electrode material is higher than that of silicon-containing negative electrode material. For the same type of lithium-carbon material with a cocoon structure, the actual demand for graphite negative electrode material is smaller, preferably 1g:(10-200)mg. When the mass ratio is too small, that is, when the mass of the lithium-carbon material in the cocoon structure is relatively large, the pre-lithiation negative electrode not only has the effect of pre-lithiation, but also has the function of storing lithium sources, showing the characteristics of a composite negative electrode. During the battery cycle, the lithium source can be continuously replenished, further improving the cycle performance and energy density of the pre-lithiation negative electrode.
[0024] Optionally, the thickness of the pre-lithium layer is not greater than the thickness of the negative electrode active material layer. This arrangement achieves lithium replenishment while taking into account the energy density of the negative electrode.
[0025] Optionally, the pre-lithium layer includes a continuous pre-lithium layer and / or an intermittent pre-lithium layer.
[0026] Optionally, the intermittent pre-lithium layer includes a pre-lithium area and a blank area, and the width ratio of the pre-lithium area to the blank area is (0.5-10):1, for example, it can be 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 2:1, 3:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 7.5:1, 9:1, 9.5:1 or 10:1, etc., preferably (1-5):1.
[0027] Optionally, the thickness of the pre-lithium layer is not higher than 20% of the total thickness of the pre-lithiation negative electrode, for example, it can be 20%, 18%, 15%, 12%, 10%, 7%, 5%, 3% or 1%, etc., including but not limited to the point value. The thickness of the lithium supplement layer can take into account both the pre-lithiation effect and the energy density of the negative electrode, and can be selected according to the type of negative electrode active material, the type of lithium-carbon material with a cocoon structure, the first coulomb efficiency and actual needs, preferably not higher than 10%. When the thickness of the pre-lithium layer is too large, that is, when the mass of the lithium-carbon material with a cocoon structure is large, the pre-lithiation negative electrode has the function of storing lithium source in addition to the pre-lithiation effect, showing the characteristics of a composite negative electrode. During the battery cycle, the lithium source can be continuously supplemented, further improving the cycle performance and energy density of the pre-lithiation negative electrode.
[0028] For the technical solution in which the lithium-carbon material exists in the negative electrode active material layer, the pre-lithiation method of the present invention may include the following steps:
[0029] (1) mixing a structural carbon material, lithium-containing particles and an organic solvent, and then spray drying or stirring at a rotation speed of more than 5000 rpm to obtain a lithium-carbon material with a cocoon structure;
[0030] (2) mixing the negative electrode active material, the conductive agent and the first binder, and then fiberizing the binder to obtain a first mixture, and then mixing the first mixture with a lithium-carbon material with a cocoon structure to obtain a second mixture, hot pressing the second mixture into a negative electrode active material layer, and then compounding it with a current collector to obtain the pre-lithiation negative electrode;
[0031] Alternatively, the negative electrode active material, the conductive agent, the second binder, the cocoon-structured lithium-carbon material and the organic solvent are mixed to prepare a negative electrode slurry, and then the negative electrode slurry is coated on the surface of the current collector to obtain the pre-lithiation negative electrode.
[0032] In the present invention, regardless of whether a dry method (without using an organic solvent) or a wet method (using an organic solvent) is used, a cocoon-structured lithium-carbon material can be used as a lithium source, which is mixed into the electrode system during the mixing process to directly prepare a pre-lithiated negative electrode. Preferably, the pre-lithiated negative electrode is prepared by a dry method, and the dry method can prepare a negative electrode with a high energy density.
[0033] Optionally, step (1) further comprises the following operations: (a) mixing lithium-containing particles, an organic lithium ion transport agent and a conductive agent to form particles consisting of lithium-containing particles and an organic conductive layer coated on the surface thereof;
[0034] (b) uniformly mixing the obtained particles with the structural carbon material in an organic solvent, and then spray drying or high-speed stirring to obtain a lithium-carbon material with a cocoon structure. The operation constructs an organic ion conductive layer on the surface of the lithium-containing particles, which is conducive to the diffusion of lithium ions and further improves the ionic conductivity of the pre-lithiation negative electrode.
[0035] Alternatively, the mixing of the lithium-containing particles, the organic lithium ion transport agent and the conductive agent can be carried out in the presence of an organic solvent, and then the solvent is removed. The organic solvent can include N-methylpyrrolidone (NMP), ethanol, n-hexane, liquid paraffin, tetrahydrofuran, p-xylene, etc.
[0036] Optionally, the organic solvent in step (1) is any one of N-methylpyrrolidone, liquid alkane with 5 to 10 carbon atoms, benzene, p-xylene or petroleum ether, or a combination of at least two thereof.
[0037] Optionally, the spray drying conditions in step (1) include: an air inlet temperature of 180-240°C, for example, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 215°C or 220°C, etc., preferably 200-220°C; an air outlet temperature of 90-110°C, for example, 90°C, 95°C, 100°C, 105°C or 110°C, etc., preferably 100-110°C; an atomization pressure of 0.1-0.5Mpa, for example, 0.2Mpa, 0.25Mpa, 0.3Mpa, 0.35Mpa or 0.4Mpa, etc., preferably 0.2-0.4Mpa.
[0038] Optionally, the speed of the high-speed stirring in step (1) is 6000-15000 rpm, and the time is 0.5-10 min. For example, the speed can be 6000 rpm, 6500 rpm, 7000 rpm, 75000 rpm, 8000 rpm, 8500 rpm, 9000 rpm, 10000 rpm, 11000 rpm, 11500 rpm,
[0039] 12000rpm, 12500rpm, 13000rpm, 14000rpm, 14500rpm or 15000rpm, etc., and the time can be 0.5min, 1min, 1.5min, 2min, 2.5min, 3min, 3.5min, 4min, 4.5min, 5min, 6min, 7min, 8min, 9min, 9.5min or 10min, etc., preferably the speed is 8000-12000rpm, and the time is 1-5min.
[0040] Optionally, in step (2), the first binder includes any one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polyisobutylene, polytetrafluoroethylene or sodium carboxymethyl cellulose, or a combination of at least two thereof.
[0041] Optionally, the organic solvent in step (2) comprises any one or a combination of at least two of N-methylpyrrolidone, liquid alkanes with 5 to 10 carbon atoms, benzene, p-xylene or petroleum ether, preferably any one or a combination of at least two of p-xylene, n-hexane or heptane.
[0042] In the present invention, the type of the conductive agent is not specifically limited, and the conductive agent includes but is not limited to any one or a combination of at least two of acetylene black, Ketjen black, conductive graphite, Cabot black or Super P. As long as it is a type commonly used by those skilled in the art, it can be used in the present invention.
[0043] In the present invention, the type of binder is not specifically limited, and the second binder includes, but is not limited to, any one or a combination of at least two of polyvinylidene fluoride, styrene-butadiene rubber, polystyrene, polyisobutylene, styrene-butadiene-styrene block copolymer, or styrene-ethylene-butylene-styrene block copolymer. As long as it is a type commonly used by those skilled in the art, it can be used in the present invention.
[0044] Optionally, the mass ratio of the conductive agent, the first binder or the second binder and the negative electrode active material is (1-10): (1-10): (80-98), preferably (2-5): (2-5): (90-96).
[0045] As a preferred technical solution of the present invention, the steps for preparing the negative electrode slurry in step (2) are as follows:
[0046] (a) mixing a negative electrode active material, a conductive agent, a second binder and an organic solvent, and then adding a lithium carbon material with a cocoon structure for secondary mixing to prepare a negative electrode slurry;
[0047] The secondary mixing time is 30-60 min, and the secondary mixing speed is 3000-5000 rpm; the mixing time can be 30 min, 35 min, 40 min, 45 min, 50 min,
[0048] 55min or 60min, etc., the speed can be 3000rpm, 3200rpm, 3500rpm,
[0049] 4000rpm, 4500rpm, 4800rpm or 5000rpm, etc. The mixing time and rotation speed include but are not limited to the listed point values and are adjusted according to the actual process.
[0050] (b) coating the negative electrode slurry on the surface of the current collector to obtain the pre-lithiation negative electrode.
[0051] Regarding the technical solution of forming a pre-lithium layer from a lithium-carbon material, the pre-lithiation method of the present invention may include the following steps:
[0052] (1) mixing a structural carbon material, lithium-containing particles and an organic solvent, and then spray drying or stirring at a rotation speed of more than 5000 rpm to obtain a lithium-carbon material with a cocoon structure;
[0053] (2) disposing a lithium-carbon material with a cocoon structure on at least one side of a current collector, wherein the disposing method includes coating and / or rolling to obtain a pre-lithium layer-current collector complex;
[0054] (3) mixing the negative electrode active material, the conductive agent and the first binder, and then fiberizing the binder to obtain a mixture, and then hot pressing the mixture into a negative electrode active material layer, and then compounding with a pre-lithiation layer-current collector complex to obtain the pre-lithiation negative electrode;
[0055] Alternatively, the negative electrode active material, the conductive agent, the second binder and the organic solvent are mixed to prepare a negative electrode slurry, and then the negative electrode slurry is coated on the surface of the pre-lithiation layer-current collector complex to obtain the pre-lithiation negative electrode.
[0056] In the present invention, whether a dry method (without using an organic solvent) or a wet method (using an organic solvent) is used, a negative electrode active material layer can be arranged on the surface of the pre-lithiation layer-current collector complex to obtain a pre-lithiation negative electrode. The dry method is preferably used to prepare the pre-lithiation negative electrode.
[0057] Optionally, step (1) further comprises the following operations: (a) mixing lithium-containing particles, an organic lithium ion transport agent and a conductive agent to form particles consisting of lithium-containing particles and an organic conductive layer coated on the surface thereof;
[0058] (b) uniformly mixing the obtained particles with the structural carbon material in an organic solvent, and then spray drying or high-speed stirring to obtain a lithium-carbon material with a cocoon structure. The operation constructs an organic ion conductive layer on the surface of the lithium-containing particles, which is conducive to the diffusion of lithium ions and further improves the ionic conductivity of the pre-lithiation negative electrode.
[0059] Alternatively, the mixing of the lithium-containing particles, the organic lithium ion transport agent and the conductive agent can be carried out in the presence of an organic solvent, and then the solvent is removed. The organic solvent can include N-methylpyrrolidone (NMP), ethanol, n-hexane, liquid paraffin, tetrahydrofuran, p-xylene, etc.
[0060] The mass ratio of the lithium-containing particles, the organic lithium ion transport agent and the conductive agent is (80-95): (1-10): (0.1-10), preferably (90-95): (5-10) (0.5-5).
[0061] Optionally, the organic solvent in step (1) is any one of N-methylpyrrolidone, liquid alkane with 5 to 10 carbon atoms, benzene, p-xylene or petroleum ether, or a combination of at least two thereof.
[0062] Optionally, the spray drying conditions in step (1) include: an air inlet temperature of 180-240°C, for example, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 215°C or 220°C, etc., preferably 200-220°C; an air outlet temperature of 90-110°C, for example, 90°C, 95°C, 100°C, 105°C or 110°C, etc., preferably 100-110°C; an atomization pressure of 0.1-0.5Mpa, for example, 0.2Mpa, 0.25Mpa, 0.3Mpa, 0.35Mpa or 0.4Mpa, etc., preferably 0.2-0.4Mpa.
[0063] Optionally, the speed of the high-speed stirring in step (1) is 6000-15000 rpm, and the time is 0.5-10 min. For example, the speed can be 6000 rpm, 6500 rpm, 7000 rpm, 75000 rpm, 8000 rpm, 8500 rpm, 9000 rpm, 10000 rpm, 11000 rpm, 11500 rpm,
[0064] 12000rpm, 12500rpm, 13000rpm, 14000rpm, 14500rpm or 15000rpm, etc., and the time can be 0.5min, 1min, 1.5min, 2min, 2.5min, 3min, 3.5min, 4min, 4.5min, 5min, 6min, 7min, 8min, 9min, 9.5min or 10min, etc., preferably the speed is 8000-12000rpm, and the time is 1-5min.
[0065] In the present invention, the mixture is obtained by high-speed stirring in step (1), and the mixture can be separated and dried to obtain a dry core-shell lithium-carbon material, which can be directly compounded on the surface of the current collector by mechanical rolling, or the mixture can be directly coated on the surface of the current collector; the core-shell lithium-carbon material obtained by spray drying can be directly compounded on the surface of the current collector by mechanical rolling, or it can be dispersed in a solvent for coating. The specific manner in which the core-shell lithium-carbon material is arranged on the surface of the current collector is not specifically limited, as long as it is arranged on the surface of the current collector, it belongs to the protection scope of the present invention.
[0066] Optionally, in step (3), the first binder includes any one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polyisobutylene, polytetrafluoroethylene or sodium carboxymethyl cellulose, or a combination of at least two thereof.
[0067] Optionally, the organic solvent in step (3) comprises any one or a combination of at least two of N-methylpyrrolidone, liquid alkanes with 5 to 10 carbon atoms, benzene, p-xylene or petroleum ether, preferably any one or a combination of at least two of p-xylene, n-hexane or heptane.
[0068] In the present invention, the type of the conductive agent is not specifically limited, and the conductive agent includes but is not limited to any one or a combination of at least two of acetylene black, Ketjen black, conductive graphite, Cabot black or Super P. As long as it is a type commonly used by those skilled in the art, it can be used in the present invention.
[0069] In the present invention, the type of binder is not specifically limited, and the second binder includes, but is not limited to, any one or a combination of at least two of polyvinylidene fluoride, styrene-butadiene rubber, polystyrene, polyisobutylene, styrene-butadiene-styrene block copolymer, or styrene-ethylene-butylene-styrene block copolymer. As long as it is a type commonly used by those skilled in the art, it can be used in the present invention.
[0070] The mass ratio of the conductive agent, the first binder or the second binder and the negative electrode active material is (1-10): (1-10): (80-98), preferably (2-5): (2-5): (90-96).
[0071] Compared with the prior art, the present invention has at least one of the following beneficial effects:
[0072] (1) The pre-lithiation negative electrode provided by the present invention adopts a lithium-carbon material with a cocoon structure as a lithium replenisher, which is evenly mixed with the negative electrode active material and has good contact, and does not form obvious voids in the negative electrode to increase the internal resistance. The pre-lithiation negative electrode has a high first coulombic efficiency and structural stability; or, a pre-lithiation layer is provided on the surface of the current collector, and the thickness can be controlled to be less than 5 μm, so that a stable electron path is provided while achieving precise lithium replenishment, and the utilization rate of the pre-lithiation agent is high. The pre-lithiation negative electrode has a high first coulombic efficiency and excellent cycle performance;
[0073] (2) The present invention further improves the initial coulombic efficiency and cycle performance of the pre-lithiation negative electrode by selecting the type of lithium-containing particles and regulating parameters such as the mass ratio of lithium-carbon material to lithium-containing particles;
[0074] (3) The preparation method provided by the present invention is simple to operate and has high production efficiency. In particular, the coating process is different from the existing process, and the solvent and binder used are friendly to metallic lithium, providing a new idea for accurate lithium replenishment of the negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] Figure 1 A schematic diagram of a pre-lithiation negative electrode prepared by the pre-lithiation method of the present invention;
[0076] 1-current collector, 2-negative electrode active material, 3-lithium-carbon material with cocoon structure.
[0077] Figure 2 A schematic diagram of another pre-lithiation negative electrode prepared by the pre-lithiation method of the present invention;
[0078] 1-current collector, 4-pre-lithium layer, 5-negative electrode active material layer.
[0079] Figure 3 This is the SEM image of the lithium-carbon material with a cocoon structure in Example 4. DETAILED DESCRIPTION
[0080] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0081] Figure 1It is a schematic diagram of a pre-lithiation negative electrode prepared by the pre-lithiation method of the present invention, wherein the pre-lithiation negative electrode comprises a current collector 1, wherein a negative electrode active substance 2 and a lithium-carbon material 3 with a cocoon structure are arranged on the surface of the current collector 1, wherein the lithium-carbon material 3 with a cocoon structure is distributed between the negative electrode active substances 2 and is evenly mixed, wherein the lithium-carbon material with a cocoon structure comprises a cocoon body formed by a structural carbon material and one or more lithium-containing particles contained in the cocoon body (refer to the SEM image in Example 4), wherein the cocoon body has good contact with the negative electrode active substance 2 and constructs a good electron path, wherein no obvious voids are formed in the negative electrode after lithium supplementation, thereby increasing the internal resistance, and the pre-lithiation negative electrode has a high first coulomb efficiency and structural stability.
[0082] Figure 2 It is a schematic diagram of another pre-lithiation negative electrode prepared by the pre-lithiation method of the present invention, the pre-lithiation negative electrode comprises a current collector 1, a pre-lithiation layer 2 is arranged on the surface of the current collector 1, the pre-lithiation layer 2 comprises a pre-lithiation agent using a lithium-carbon material with a cocoon structure as a raw material, a negative electrode active material layer 3 is arranged on the surface of the pre-lithiation layer, and the thickness of the pre-lithiation layer is not higher than 20% of the total thickness of the pre-lithiation negative electrode. While achieving accurate lithium replenishment, a stable electron path is provided, the utilization rate of the pre-lithiation agent is high, and the pre-lithiation negative electrode has a high first coulomb efficiency and excellent cycle performance.
[0083] Example 1
[0084] This embodiment provides a pre-lithiation method, wherein the negative electrode obtained by the pre-lithiation method includes graphite and a lithium-carbon material with a cocoon structure, wherein the lithium-carbon material with a cocoon structure is distributed between the graphites.
[0085] The pre-lithiation method comprises the following steps:
[0086] (1) Graphene (XF001W 7440-44-0, Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.), multi-walled carbon nanotubes (XFM01 1333-86-4, Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.), Cabot BP2000, metal lithium powder with an average particle size of 5 μm and n-hexane were mixed, and the mass ratio of the total mass of graphene, multi-walled carbon nanotubes and Cabot BP2000 to the metal lithium powder was 1:1000, and then high-speed dispersion was performed at a rotation speed of 5000 rpm for 10 minutes to obtain a lithium-carbon material with a cocoon structure;
[0087] (2) Graphite, acetylene black, and styrene-butadiene rubber (SBR, 1502, Sinopec Jilin Chemical) were mixed in quantities of 800 g, 100 g, and 100 g, with n-hexane as the solvent, to prepare a first slurry, and then 8 g of a lithium-carbon material with a cocoon structure was added, and the mixture was stirred at a speed of 3000 rpm for 60 min to obtain a second slurry, and then the second slurry was coated on a surface of a 6 μm carbon-coated copper foil and dried to obtain the pre-lithiation negative electrode.
[0088] Example 2
[0089] This embodiment provides a pre-lithiation method, wherein the negative electrode obtained by the pre-lithiation method includes silicon-carbon and a lithium-carbon material with a cocoon structure, wherein the lithium-carbon material with a cocoon structure is distributed between the silicon-carbon.
[0090] The pre-lithiation method comprises the following steps:
[0091] (1) acetylene black, polyethylene oxide (Aladdin, P432440) and metal lithium powder are mixed in p-xylene in a mass ratio of 5:5:90, and the p-xylene is removed by drying to form metal lithium powder containing an organic conductive layer;
[0092] (2) mixing single-walled carbon nanotubes, metal lithium powder with an average particle size of 45 μm and an organic conductive layer, and n-hexane, wherein the mass ratio of the single-walled carbon nanotubes to the metal lithium powder is 1:500, and then dispersing at a high speed of 8000 rpm for 8 minutes to obtain a lithium-carbon material with a cocoon structure;
[0093] (3) Silicon carbon (Bai Te Rui, DXB8), carbon fiber, and polyvinylidene fluoride (Su Wei, 5130) were mixed in masses of 800g, 100g, and 100g, with N-methylpyrrolidone as the solvent, to prepare a first slurry, and then 160g of lithium carbon material with a cocoon structure was added, and stirred at a speed of 4500rpm for 45min to obtain a second slurry, and then the second slurry was coated on the surface of 6μm carbon nanotube paper and dried to obtain the pre-lithiation negative electrode.
[0094] Example 3
[0095] This embodiment provides a pre-lithiation method, wherein the negative electrode obtained by the pre-lithiation method includes silicon oxygen and a lithium-carbon material with a cocoon structure, wherein the lithium-carbon material with a cocoon structure is distributed between the silicon oxygen.
[0096] The pre-lithiation method comprises the following steps:
[0097] (1) carbon nanofibers (Aladdin, C478418), conductive graphite KS-6, lithium-magnesium alloy particles with an average particle size of 100 μm (magnesium mass fraction of 10%) and p-xylene are mixed, and the mass ratio of the total mass of single-walled carbon nanotubes and conductive carbon black to the metal lithium powder is 1:100, and then high-speed dispersion is carried out at a speed of 12000 rpm for 5 minutes to obtain a lithium-carbon material with a cocoon structure;
[0098] (2) Silicon oxide (Bai Te Rui, DXA5), Super P, and polyisobutylene (Aladdin, P418837) were mixed in masses of 800g, 100g, and 100g, with heptane as the solvent, to prepare a first slurry, and then 240g of lithium-carbon material with a cocoon structure was added, and stirred at a speed of 4500rpm for 45min to obtain a second slurry, and then the second slurry was coated on the surface of a 6μm perforated copper foil and dried to obtain the pre-lithiation negative electrode.
[0099] Example 4
[0100] This embodiment provides a pre-lithiation method, wherein the negative electrode obtained by the pre-lithiation method includes graphite and a lithium-carbon material with a cocoon structure, wherein the lithium-carbon material with a cocoon structure is distributed between the graphites.
[0101] The pre-lithiation method comprises the following steps:
[0102] (1) Single-walled carbon nanotubes (XFS02 1333-86-4, Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.), metal lithium powder with an average particle size of 50 μm and n-hexane were mixed, and the mass ratio of the single-walled carbon nanotubes to the metal lithium powder was 1:500, and then spray-dried, with an inlet air temperature of 220° C., an outlet air temperature of 100° C., and an atomization pressure of 0.5 MPa to obtain a cocoon-structured lithium-carbon material; the SEM characterization of the cocoon-structured lithium-carbon material is as follows: Figure 3 As shown, it can be clearly seen from the figure that the single-walled carbon nanotubes are wound around the surface of the metal lithium powder to form a cocoon body, and the cocoon body contains the metal lithium powder to form a lithium-carbon material with a cocoon structure;
[0103] (2) Graphite, acetylene black, and polytetrafluoroethylene are mixed in weights of 900 g, 50 g, and 50 g, and then processed by ultra-strong shearing equipment to fiberize the polytetrafluoroethylene binder. 180 g of lithium-carbon material with a silkworm cocoon structure is added, and a 120 μm thick negative electrode film is obtained by extrusion and calendaring at 80° C. The negative electrode film is composited with a carbon-coated copper foil by hot pressing to obtain the pre-lithiation negative electrode.
[0104] Example 5
[0105] Compared with Example 4, the only difference is that the mass of the cocoon-structured lithium-carbon material in step (2) is replaced with 0.9 g, and the other conditions are the same.
[0106] Example 6
[0107] Compared with Example 4, the only difference is that the mass of the cocoon-structured lithium-carbon material in step (2) is replaced with 300 g, and the other conditions are the same.
[0108] Example 7
[0109] Compared with Example 4, the only difference is that the metallic lithium powder in step (1) is replaced by lithium-indium alloy powder, the mass fraction of indium is 20%, and the other conditions are the same.
[0110] Comparative Example 1
[0111] Compared with Example 4, the only difference is that the cocoon-structured lithium-carbon material in step (2) is replaced by the metallic lithium powder in step (1), and the other conditions remain unchanged.
[0112] Comparative Example 2
[0113] Compared with Example 4, the only difference is that the lithium-carbon material with a cocoon structure is not added in step (2), and the other conditions remain unchanged.
[0114] Comparative Example 3
[0115] Compared with Example 4, the only difference is that the rotation speed in step (1) is replaced with 2000 rpm, and the other conditions remain unchanged. At the rotation speed, the single-walled carbon nanotubes can be fully mixed with the metal lithium powder, but no cocoon structure is formed.
[0116] Negative electrode performance test:
[0117] The negative electrodes of Examples 1-7 and Comparative Examples 1-3 were assembled into soft-pack batteries with nickel cobalt manganese oxide positive electrodes for testing. The first coulombic efficiency and cycle test data at 0.2C are shown in Table 1 below.
[0118] Table 1
[0119]
[0120] From Table 1, we can see that:
[0121] (1) Based on Examples 4-6, it can be seen that the degree of pre-lithiation is closely related to the amount of cocoon-structured lithium-carbon material used. When the amount is small (Example 5), the improvement of the first coulombic efficiency and cycle performance is not obvious; when the amount is too much (Example 6), the first coulombic efficiency and cycle performance are significantly improved, but it is not conducive to the preparation of a high energy density battery.
[0122] (2) Combining Example 4 and Example 7, it can be seen that the first coulombic efficiency of the battery corresponding to Example 4 is close to that of Example 7, and the cycle performance is worse than that of Example 7. This is because lithium indium alloy is used for lithium supplementation in Example 7. Indium can regulate the deposition of metallic lithium and conduct electrons at the same time, cooperating with the structural carbon material single-walled carbon nanotubes, so that the negative electrode exhibits excellent cycle performance.
[0123] (3) Based on Example 4 and Comparative Examples 1-3, it can be seen that when the same mass of lithium supplement is added, the pre-lithiation agents with different structures have different degrees of improvement in the initial coulombic efficiency of the negative electrode and the improvement in the cycle performance. The core-shell structured lithium-carbon material of the present invention is used as a lithium supplement. The cocoon-structured lithium-carbon material contains a structural carbon material with good conductivity and a certain rigidity, which can improve the conductivity and structural stability of the pre-lithiation negative electrode, so that the pre-lithiation negative electrode has a higher initial coulombic efficiency and excellent cycle performance.
[0124] Example 8
[0125] The present embodiment provides a pre-lithiation method, wherein the negative electrode obtained by the pre-lithiation method comprises a carbon-coated copper foil, a pre-lithiation layer is provided on the surface of the carbon-coated copper foil, the pre-lithiation layer comprises a pre-lithiation agent using a lithium-carbon material with a cocoon structure as a raw material, a graphite layer is provided on the surface of the pre-lithiation layer, and the thickness of the pre-lithiation layer is 3% of the total thickness of the pre-lithiation negative electrode.
[0126] The pre-lithiation method comprises the following steps:
[0127] (3) mixing graphene, multi-walled carbon nanotubes, Cabot BP2000, metal lithium powder with an average particle size of 5 μm and heptane, wherein the mass ratio of the total mass of graphene, multi-walled carbon nanotubes and Cabot BP2000 to the metal lithium powder is 1:1000, and then dispersing at a high speed of 6000 rpm for 10 min, filtering and drying to obtain a lithium-carbon material with a cocoon structure;
[0128] (4) Laying the core-shell structured lithium-carbon material on a PET film and subjecting it to mechanical rolling to form a film material, and then compounding the film material on the surface of a carbon-coated copper foil by mechanical rolling to obtain a pre-lithium layer. During the mechanical rolling process, the cocoon-structured lithium-carbon material is deformed so that the thickness of the pre-lithium layer is 3 μm, thereby obtaining a pre-lithium layer-carbon-coated copper foil composite;
[0129] (5) Graphite, acetylene black, and polyvinylidene fluoride were mixed in quantities of 800 g, 100 g, and 100 g, with N-methylpyrrolidone as the solvent, to prepare a negative electrode slurry. The negative electrode slurry was then coated on the surface of the pre-lithiation layer-carbon-coated copper foil composite, the thickness of the graphite layer was controlled to be 97 μm, and the mixture was dried to obtain the pre-lithiation negative electrode.
[0130] Example 9
[0131] The present embodiment provides a pre-lithiation method, wherein the negative electrode obtained by the pre-lithiation method comprises a perforated copper foil, a pre-lithiation layer is provided on the surface of the perforated copper foil, the pre-lithiation layer comprises a pre-lithiation agent using a lithium-carbon material with a cocoon structure as a raw material, a silicon-carbon layer is provided on the surface of the pre-lithiation layer, and the thickness of the pre-lithiation layer is 10% of the total thickness of the pre-lithiation negative electrode.
[0132] The pre-lithiation method comprises the following steps:
[0133] (1) mixing single-walled carbon nanotubes, fluorinated graphene, acetylene black, metal lithium powder with an average particle size of 50 μm containing a lithium carbonate protective layer, and p-xylene, wherein the mass ratio of the total mass of the single-walled carbon nanotubes, fluorinated graphene, and acetylene black to the metal lithium powder is 1:500, and then dispersing at a high speed of 1000 rpm for 5 minutes, spray drying, the inlet air temperature is 200° C., the outlet air temperature is 90° C., and the atomization pressure is 0.3 MPa to obtain a lithium-carbon material with a core-shell structure;
[0134] (2) Spreading a core-shell structured lithium-carbon material on the surface of a perforated copper foil, and compounding the material on the surface of the perforated copper foil by mechanical rolling to obtain a pre-lithium layer, wherein the cocoon structured lithium-carbon material is deformed during the mechanical rolling process, so that the thickness of the pre-lithium layer is 10 μm, thereby obtaining a pre-lithium layer-perforated copper foil composite;
[0135] (3) Silicon carbon, acetylene black, and styrene-butadiene rubber are mixed in quantities of 800 g, 100 g, and 100 g, with p-xylene as the solvent, to prepare a negative electrode slurry. The negative electrode slurry is then coated on the surface of the pre-lithiation layer-carbon-coated copper foil composite, the thickness of the silicon carbon layer is controlled to be 90 μm, and the mixture is dried to obtain the pre-lithiation negative electrode.
[0136] Example 10
[0137] The present embodiment provides a pre-lithiation method, wherein the negative electrode obtained by the pre-lithiation method comprises copper foam, a pre-lithiation layer is provided on the surface of the copper foam, the pre-lithiation layer comprises a pre-lithiation agent using a lithium-carbon material with a cocoon structure as a raw material, a silicon oxide layer is provided on the surface of the pre-lithiation layer, and the thickness of the pre-lithiation layer is 20% of the total thickness of the pre-lithiation negative electrode.
[0138] The pre-lithiation method comprises the following steps:
[0139] (2) mixing carbon nanofibers, conductive graphite KS-6, lithium-magnesium alloy particles with an average particle size of 100 μm (magnesium mass fraction of 10%) and heptane, wherein the mass ratio of the total mass of the carbon nanofibers and the conductive graphite KS-6 to the metallic lithium powder is 1:100, and then dispersing at a high speed of 12000 rpm for 5 min to obtain a lithium-carbon material with a cocoon structure;
[0140] (2) Laying the core-shell structured lithium-carbon material on the surface of the PP film, forming a lithium film by mechanical rolling, and then mechanically rolling and compounding it on the surface of the copper foam to obtain a pre-lithium layer. During the mechanical rolling process, the cocoon structured lithium-carbon material is deformed so that the thickness of the pre-lithium layer is 20 μm, thereby obtaining a pre-lithium layer-copper foam composite;
[0141] (3) Silicon oxide, Super P, and styrene-butadiene-styrene block copolymer are mixed in masses of 800 g, 100 g, and 100 g, and then processed by ultra-strong shearing equipment to fiberize the styrene-butadiene-styrene block copolymer, and an 80 μm thick negative electrode film is obtained by extrusion and calendaring at 80° C. The negative electrode film pre-lithiation layer-foam copper composite is composited by hot pressing to obtain the pre-lithiation negative electrode.
[0142] Embodiment 11
[0143] Compared with Example 9, the only difference is that the structural carbon materials single-walled carbon nanotubes, fluorinated graphene, and acetylene black in step (1) are replaced by single-walled carbon nanotubes and fluorinated graphene, and the other conditions remain unchanged.
[0144] Example 12
[0145] Compared with Example 9, the only difference is that the structural carbon materials single-walled carbon nanotubes, fluorinated graphene, and acetylene black in step (1) are replaced by single-walled carbon nanotubes and acetylene black, and the other conditions remain unchanged.
[0146] Embodiment 13
[0147] Compared with Example 9, the only difference is that the structural carbon material single-walled carbon nanotubes, fluorinated graphene, and acetylene black in step (1) are replaced by single-walled carbon nanotubes, and the other conditions remain unchanged.
[0148] Embodiment 14
[0149] Compared with Example 9, the only difference is that the metallic lithium powder in step (1) is replaced by lithium-magnesium alloy powder, the mass fraction of magnesium is 20%, and the other conditions are the same.
[0150] Embodiment 15
[0151] Compared with Example 9, the only difference is that the thickness of the pre-lithium layer in step (2) is replaced with 1 μm, and the other conditions are the same.
[0152] Example 16
[0153] Compared with Example 9, the only difference is that the thickness of the pre-lithium layer in step (2) is replaced with 30 μm, and the other conditions are the same.
[0154] Comparative Example 4
[0155] Compared with Example 9, the only difference is that the cocoon-structured lithium-carbon material in step (2) is replaced by the metallic lithium powder in step (1) (ie, the pre-lithium layer uses metallic lithium powder as the pre-lithium agent), and the other conditions remain unchanged.
[0156] Comparative Example 5
[0157] Compared with Example 9, the only difference is that the negative electrode slurry in step (3) is coated on the surface of the current collector to obtain the negative electrode (ie, the negative electrode does not contain a pre-lithium layer), and the other conditions remain unchanged.
[0158] Comparative Example 6
[0159] Compared with Example 9, the only difference is that the rotation speed in step (1) is replaced with 2000 rpm, and the other conditions remain unchanged. At the rotation speed, the single-walled carbon nanotubes, fluorinated graphene, and acetylene black can be fully mixed with the metallic lithium powder, but no cocoon structure is formed.
[0160] Comparative Example 7
[0161] Compared with Example 9, the only difference is that a silicon carbon layer is provided on the surface of the current collector, and a pre-lithium layer is provided on the surface of the silicon carbon layer, and other conditions are the same.
[0162] Negative electrode performance test:
[0163] The negative electrodes of Examples 8-16 and Comparative Examples 4-7 were assembled into soft-pack batteries with the positive electrodes of nickel cobalt manganese oxide. The first coulombic efficiency and cycle test data at 0.2C are shown in Table 2 below.
[0164] Table 2
[0165]
[0166]
[0167] From Table 2, we can see that:
[0168] (1) Combining Example 9 and Examples 11-13, it can be seen that the first coulombic efficiency and cycle performance of the battery corresponding to Example 9 are better than those of Examples 11-13. This is because the structural carbon material in Example 9 includes linear single-walled carbon nanotubes, flaky fluorinated graphene and granular acetylene black. The linear single-walled carbon nanotubes are the skeleton, the flaky fluorinated graphene is connected between the skeletons, and the granular acetylene black is filled in the gaps of the skeleton or loaded on the surface of the skeleton. The three carbon materials with different structures construct a good three-dimensional conductive network, and the utilization rate of the pre-lithium agent is high.
[0169] (2) Combining Example 9 and Example 14, it can be seen that the first coulombic efficiency of the battery corresponding to Example 9 is slightly higher than that of Example 14, and the cycle performance is worse than that of Example 14. This is because lithium-magnesium alloy is used for lithium supplementation in Example 14. Magnesium can regulate the deposition of metallic lithium and conduct electrons, and cooperate with the structural carbon material, so that the negative electrode exhibits excellent cycle performance.
[0170] (3) It can be seen from Example 9 and Examples 15-16 that the thickness of the pre-lithiation layer has a great influence on the initial coulombic efficiency and cycle performance of the pre-lithiation negative electrode. If the thickness is too small (Example 15), the pre-lithiation effect is limited; if the thickness is too large (Example 16), more inactive substances are introduced, which reduces the energy density of the pre-lithiation negative electrode.
[0171] (4) Based on Example 9 and Comparative Examples 4-7, it can be seen that the first coulombic efficiency and cycle performance of the battery corresponding to Example 9 are better than those of Comparative Examples 4-7. This is because Comparative Example 4 uses metallic lithium powder for pre-lithiation, which is prone to electronic path disconnection, the pre-lithiation process ends prematurely, and the utilization rate of metallic lithium powder is low; Comparative Example 5 is not pre-lithiation, and its characterization is the performance of the silicon-carbon material itself; Comparative Example 6 uses a mixture of carbon material and metallic lithium powder randomly mixed, rather than the core-shell structure formed by metallic lithium powder and carbon material in the present invention. Although it can also improve the electrochemical performance, it cannot fully pre-lithiate, and the utilization rate of metallic lithium powder is lower than that of Example 9; Comparative Example 7 places the pre-lithiation layer on the surface of the negative electrode, and the pre-lithiation layer is in direct contact with the environment and is easily oxidized or contaminated.
[0172] The applicant declares that the present invention illustrates the detailed structural features of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed structural features, that is, it does not mean that the present invention must rely on the above-mentioned detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A pre-lithiation method, characterized in that: The pre-lithiation method comprises using a lithium-carbon material having a cocoon structure as a pre-lithiation material to pre-lithiate an electrode to form a pre-lithiation electrode. The cocoon-structured lithium-carbon material comprises a cocoon body formed of a structural carbon material and one or more lithium-containing particles contained in the cocoon body.
2. The pre-lithiation method according to claim 1, characterized in that: The electrode is a negative electrode, and the negative electrode active material includes any one of graphite, tin-based materials, hard carbon, soft carbon, activated carbon, mesophase carbon microspheres, silicon-carbon materials or silicon-oxygen materials, or a combination of at least two thereof.
3. The pre-lithiation method according to claim 1, characterized in that: The structural carbon material is any one or a combination of at least two of granular, linear or flaky nanocarbon materials, and the structural carbon material includes any one or a combination of at least two of acetylene black, Ketjen black, Cabot BP2000, Super P, single-walled carbon nanotubes, few-walled carbon nanotubes, multi-walled carbon nanotubes, doped carbon nanotubes, graphene, doped graphene, carbon nanofibers or doped carbon nanofibers; The doping elements in the doped carbon nanotubes, doped graphene or doped carbon nanofibers independently include any one of fluorine, nitrogen, oxygen, phosphorus, silver, silicon, tin or zinc, or a combination of at least two of them.
4. The pre-lithiation method according to claim 1, characterized in that: The lithium-containing particles include metal lithium particles and / or metal lithium alloy particles, and the mass content of metal lithium in the metal lithium alloy particles is not less than 70%; Wherein, the average particle size of the lithium-containing particles is 1-100 microns; Among them, the metallic lithium alloy particles include binary lithium alloy and / or ternary lithium alloy, the binary lithium alloy powder includes any one of lithium magnesium alloy, lithium boron alloy, lithium silver alloy, lithium indium alloy, lithium silicon alloy, lithium aluminum alloy or lithium tin alloy, or a combination of at least two of them; the ternary lithium alloy powder includes any one of lithium tin silver alloy, lithium silver silicon alloy or lithium boron zinc alloy, or a combination of at least two of them.
5. The pre-lithiation method according to claim 1, characterized in that: The cocoon structure further comprises an organic conductive layer disposed between the lithium-containing particles and the structural carbon material, wherein the organic conductive layer comprises an organic ion conductive agent and a conductive agent; The conductive agent comprises at least one of carbon nanotubes, carbon black, graphene and acetylene black; The organic lithium ion transport agent includes polyethylene oxide, polyethylene glycol, polysiloxane, polytrimethylene carbonate, polycarbonate, polyethylene carbonate, polypropylene carbonate, polyvinylene carbonate, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, poly(vinylidene fluoride-hexafluoropropylene), polyphenylene sulfide, para-benzoquinone, and a copolymer or mixture of at least two of the above polymers.
6. The pre-lithiation method according to claim 2, characterized in that: The lithium-carbon material having a cocoon structure is present in the negative electrode active material layer and is distributed between the negative electrode active materials, or The lithium-carbon material with a cocoon structure forms a pre-lithium layer, which is located between the negative electrode active material layer and the current collector, and the thickness of the pre-lithium layer is no more than 20% of the total thickness of the pre-lithiation negative electrode.
7. The pre-lithiation method according to claim 6, characterized in that: The pre-lithiation method comprises the following steps: (1) mixing a structural carbon material, lithium-containing particles and an organic solvent, and then spray drying or stirring at a rotation speed of more than 5000 rpm to obtain a lithium-carbon material with a cocoon structure; (2) mixing the negative electrode active material, the conductive agent and the first binder, and then fiberizing the binder to obtain a first mixture, and then mixing the first mixture with a lithium-carbon material with a cocoon structure to obtain a second mixture, hot pressing the second mixture into a negative electrode active material layer, and then compounding it with a current collector to obtain the pre-lithiation negative electrode; Alternatively, the negative electrode active material, the conductive agent, the second binder, the cocoon-structured lithium-carbon material and the organic solvent are mixed to prepare a negative electrode slurry, and then the negative electrode slurry is coated on the surface of the current collector to obtain the pre-lithiation negative electrode.
8. The method according to claim 7, characterized in that The organic solvent in step (1) is any one of N-methylpyrrolidone, liquid alkane with 5 to 10 carbon atoms, benzene, p-xylene or petroleum ether, or a combination of at least two thereof; In step (2), the first binder includes any one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polytetrafluoroethylene or sodium carboxymethyl cellulose, or a combination of at least two thereof; The organic solvent in step (2) includes any one of N-methylpyrrolidone, liquid alkanes with 5 to 10 carbon atoms, benzene, p-xylene or petroleum ether, or a combination of at least two thereof; The conductive agent in step (2) includes any one of acetylene black, Ketjen black, conductive graphite, Cabot black or Super P, or a combination of at least two thereof; In step (2), the second binder comprises any one of polyvinylidene fluoride, styrene-butadiene rubber, polystyrene, polyisobutylene, styrene-butadiene-styrene block copolymer or styrene-ethylene-butylene-styrene block copolymer, or a combination of at least two thereof; The mass ratio of the conductive agent, the first binder or the second binder and the negative electrode active material is (1-10): (1-10): (80-98).
9. The pre-lithiation method according to claim 6, characterized in that: The pre-lithiation method comprises the following steps: (1) mixing a structural carbon material, lithium-containing particles and an organic solvent, and then spray drying or stirring at a rotation speed of more than 5000 rpm to obtain a lithium-carbon material with a cocoon structure; (2) disposing a lithium-carbon material with a cocoon structure on at least one side of a current collector, wherein the disposing method includes coating and / or rolling to obtain a pre-lithium layer-current collector complex; (3) mixing the negative electrode active material, the conductive agent and the first binder, and then fiberizing the binder to obtain a mixture, and then hot pressing the mixture into a negative electrode active material layer, and then compounding with a pre-lithiation layer-current collector complex to obtain the pre-lithiation negative electrode; Alternatively, the negative electrode active material, the conductive agent, the second binder and the organic solvent are mixed to prepare a negative electrode slurry, and then the negative electrode slurry is coated on the surface of the pre-lithiation layer-current collector complex to obtain the pre-lithiation negative electrode.
10. The pre-lithiation method according to claim 9, characterized in that: The organic solvent in step (1) is any one of N-methylpyrrolidone, liquid alkane with 5 to 10 carbon atoms, benzene, p-xylene or petroleum ether, or a combination of at least two thereof; In step (3), the first binder includes any one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polytetrafluoroethylene or sodium carboxymethyl cellulose, or a combination of at least two thereof; The organic solvent in step (3) includes any one of N-methylpyrrolidone, liquid alkanes with 5 to 10 carbon atoms, benzene, p-xylene or petroleum ether, or a combination of at least two thereof; The conductive agent in step (3) includes any one of acetylene black, Ketjen black, conductive graphite, Cabot black or Super P, or a combination of at least two thereof; In step (3), the second binder comprises any one of polyvinylidene fluoride, styrene-butadiene rubber, polystyrene, polyisobutylene, styrene-butadiene-styrene block copolymer or styrene-ethylene-butylene-styrene block copolymer, or a combination of at least two thereof; The mass ratio of the conductive agent, the first binder or the second binder and the negative electrode active material is (1-10): (1-10): (80-98).
Citation Information
Patent Citations
A mixture of elemental metals and carbon for energy storage devices
CN108780887B